2017
DOI: 10.1002/rra.3189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light and mixing regime on bloom‐forming phytoplankton in a subtropical reservoir

Abstract: The joint influence of local climatic and hydrological conditions on the vertical distribution of bloom-forming phytoplankton was analysed for the Salto Grande Reservoir, a large and enriched subtropical system on the Uruguay River (South America). Threshold of physical factors hindering or impeding blooms was obtained and then contrasted with worldwide observations in reservoirs at similar latitudes. Inflowing discharge, water level, and wind velocity intensity interacted with temperature, producing mixing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 61 publications
3
37
0
8
Order By: Relevance
“…The hypothesis of the existence of two independent fish populations in the area of Salto Grande is supported by previous studies of population genetics and population dynamics in P. lineatus (Fuentes et al, 2016;INIDEP, 2008;Rueda, Carriquiriborde, Monzón, Somoza, & Ortí, 2013;Sverlij, Geracitano, & Espinach Ros, 1992). This hypothesis is also supported by Paolucci (2002) (Bordet, Fontanarrosa, & O'Farrell, 2017;Bonilla et al, 2015;Chalar et al, 2002;Giannuzzi et al, 2011; Joint Technical Commission of Salto Grande, unpublished monitoring data). Bordet et al (2017) concluded that the presence of this cyanotoxin was positively correlated with the abundance of Microsystis sp.…”
Section: Direct Effects: Independence Between the Two Reproductive mentioning
confidence: 54%
“…The hypothesis of the existence of two independent fish populations in the area of Salto Grande is supported by previous studies of population genetics and population dynamics in P. lineatus (Fuentes et al, 2016;INIDEP, 2008;Rueda, Carriquiriborde, Monzón, Somoza, & Ortí, 2013;Sverlij, Geracitano, & Espinach Ros, 1992). This hypothesis is also supported by Paolucci (2002) (Bordet, Fontanarrosa, & O'Farrell, 2017;Bonilla et al, 2015;Chalar et al, 2002;Giannuzzi et al, 2011; Joint Technical Commission of Salto Grande, unpublished monitoring data). Bordet et al (2017) concluded that the presence of this cyanotoxin was positively correlated with the abundance of Microsystis sp.…”
Section: Direct Effects: Independence Between the Two Reproductive mentioning
confidence: 54%
“…: Bonilla, et al, 2015;Haakonsson, et al, 2017;Pacheco, et al, 2010;Crisci, et al, 2017). Floraciones de cianobacterias filamentosas también han sido observadas en Salto Grande, pero en mucho menor proporción (Bordet, et al, 2017). En Rocha, especialmente en la Laguna de Castillos, se han registrado floraciones de cianobacterias en varias ocasiones anteriores, principalmente especies filamentosas (Pérez, et al, 1999;Martínez, 2014;Martínez et al, 2016), al igual que en la presente temporada estival (Martínez, observación personal).…”
Section: Causas De Las Floraciones: Origen Alóctono Por Aportes Desdeunclassified
“…Se ha registrado frecuentemente la ocurrencia de floraciones del CMA en los embalses de Salto Grande y del Río Negro (e.g. : González-Piana, et al, 2017;Bordet, et al, 2017). Estas floraciones podrían ser transportadas desde los embalses hacia el tramo final del río Uruguay y luego al RdlP.…”
Section: Causas De Las Floraciones: Origen Alóctono Desde Ríos Uruguaunclassified
See 1 more Smart Citation
“…Los primeros registros de floraciones de Microcystis spp. en Uruguay fueron en el embalse de Salto Grande (Quirós y Luchini, 1982) y en la actualidad se siguen registrando floraciones en todas las estaciones del año (Bordet, et al, 2017). Asimismo, Kruk et al (2015) detectaron la presencia de floraciones de especies de Microcystis en el Río Uruguay tanto en verano como en invierno, sugiriendo que dadas las condiciones nutricionales adecuadas estos organismos son capaces de proliferar a bajas temperaturas.…”
Section: Introductionunclassified